Inês & nós em perspectiva: um jogo sério para a formação leitora e o diálogo intercultural pela mediação do mito de Inês de Castro - Sousa, Rafael Barros de (2021)
In Brazil, despite some initiatives by public and private organizations to encourage reading, awakening the population to the powers of reading is a major educational challenge. The 2016 Retratos da Leitura no Brasil survey indicated that 44% of the Brazilian population does not read and 30% have never bought a book. More recent data from the same survey (FAILLA, 2020), reveals that Brazil lost 4.6 million readers, considering a reader a person who has read a book or half of it in the course of three months. This work consists of an investigation about the contribution of the game Inês & Nós, based on the LerAtos method of training social entrepreneurial readers, for the discovery of the powers of reading through the mediations of the mythical-historical figure of Inês de Castro and the practice of interculturality. The research used three approaches: bibliographic research of the inspirational powers of the Inesian literary framework, documentary research based on the post-doctoral report of Valéria Andrade (2019) on the game "Inês&Nós", and descriptive research on the game "Inês&Nós" and its extension possibilities. As results, 3 studies were generated. The first, "Inês de Castro: a historical and inspirational myth", highlights historical facts and mythical elements involved in the episode of the life and death of Inês de Castro and ways in which this mythical figure can promote dialogues and reading and writing practices. The second, "LerAtos em Diálogos" presents a theoretical-methodological analysis of five of its attributes: Multitranscodification, Sociocultural Entrepreneurship, Innovation Environment, Freedom of the Subject, and Democratization. The third, "The Inês&Nós Valongo-Sumé Ubiquitous Active Reading Community (UABC)", describes its principles, processes, technologies and impacts on the formation of reader-authors, and brings a proposal to expand these impacts to the discovery of the powers of reading in the context of Rural Education in Cariri Paraibano. Results of the studies indicate that the game Inês & Nós and its application involving teachers and students from the cities of Valongo, in Portugal, and Sumé, in Cariri Paraibano, contribute to the formation of readers. The players consolidate a CLAU, develop skills as readers and authors, produce Inesian works adapted in text and audio, promote a Luso-Brazilian intercultural dialogue, and may expand their impact through a school radio station. A proposal for this expansion is presented.